2003
DOI: 10.5144/0256-4947.2003.191
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Interstitial Emphysema in a Full-Term Infant: Do We Know the Incidence?

Abstract: A Rejjal, Pulmonary Interstitial Emphysema in a Full-Term Infant: Do We Know the Incidence?. 2003; 23(3-4): 191-193 Pulmonary interstitial emphysema (PIE) occurs predominantly in premature infants exposed to mechanical ventilation. In the modern literature, pneumothorax is the most common form of air leak syndrome in full-term infants of average weight, while the incidence of PIE in the same age group is not known. We report a case of a fullterm infant who developed severe PIE secondary to aggressive conve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2003
2003
2003
2003

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Salama et al suggested that the incidence of air leak syndrome, particularly the pulmonary interstitial emphysema in full term infants, is vague. 4 Affected infants are usually premature and have severe respiratory insufficiency requiring a high ventilatory pressure. Lee et al reported that in 94% of cases, the air leaks would affect more than one anatomical site.…”
Section: Discussionmentioning
confidence: 99%
“…Salama et al suggested that the incidence of air leak syndrome, particularly the pulmonary interstitial emphysema in full term infants, is vague. 4 Affected infants are usually premature and have severe respiratory insufficiency requiring a high ventilatory pressure. Lee et al reported that in 94% of cases, the air leaks would affect more than one anatomical site.…”
Section: Discussionmentioning
confidence: 99%